Inhibition of Src signaling induces autophagic killing of Toxoplasma gondii via PTEN-mediated deactivation of Akt. - Alyssa Hubal; Anusha Vendhoti; Charles N Shaffer; Sarah Vos; Yalitza Lopez Corcino; Carlos S Subauste (PLoS Pathogens)
The intracellular protozoan Toxoplasma gondii manipulates host cell signaling to avoid targeting by autophagosomes and lysosomal degradation. Epidermal Growth Factor Receptor (EGFR) is a mediator of this survival strategy. However, EGFR expression is limited in the brain and retina, organs affected in toxoplasmosis. This raises the possibility that T. gondii activates a signaling mechanism independently of EGFR to avoid autophagic targeting. We report T. gondii activates Src to promote parasite survival even in cells that lack EGFR. Blockade of Src triggered LC3 and LAMP-1 recruitment around the parasitophorous vacuole (PV) and parasite killing dependent on the autophagy protein, ULK1, and lysosomal enzymes. Src promoted PI3K activation and recruitment of activated Akt to the PV membrane. T. gondii promoted Src association with PTEN, and PTEN phosphorylation at Y240, S380, T382, and T383, hallmarks of an inactive PTEN conformation known to maintain Akt activation. Blockade of parasite killing was dependent of activated Akt. Src knockdown or treatment with the Src family kinase inhibitor, Saracatinib, impaired these events, leading to PTEN accumulation around the PV and a reduction in activated Akt recruitment at this site. Saracatinib treatment in mice with pre-established cerebral and ocular toxoplasmosis promoted PTEN recruitment around tachyzoites in neural tissue impairing recruitment of activated Akt, profoundly reducing parasite load and neural histopathology that were dependent of the autophagy protein, Beclin 1. Our studies uncovered an EGFR-independent pathway activated by T. gondii that enables its survival and is central to the development of neural toxoplasmosis.